Deconstructing the Imperial Episteme: Decolonizing Knowledge Production in Program Evaluation - Satlaj Dighe; Cynthia Matthias (The Evaluation Center at Western Michigan University, 2023)
Scholars, practitioners, and activists have all contributed to the discussion of decolonization of evaluation practice in recent years as attention has increasingly focused on the persistent harms of colonization. While these discussions have led to the development of evaluation frameworks rooted in Indigenous and locally-situated understandings, values, and methods, little attention has been paid to the colonial origins of Western-based evaluation practices that continue to pervade the field. This article seeks to contribute to the conversation about decolonization by focusing on the ways in which Western social theory, born of colonizing nations, has been influenced by the processes of colonization. Drawing on scholars and theorists from the Global South, this article highlights specific apparatuses for dismantling imperial ways of thinking and ways of knowing, and proposes a path forward for evaluators who wish to grapple with the deeply imperial epistemological roots of our field of practice.